Q-SNARE protein FgSyn8 plays important role in growth, DON production and pathogenicity of Fusarium graminearum. (March 2020) - Adnan, Muhammad; Islam, Waqar; Noman, Ali; Hussain, Ansar; Anwar, Muhammad; Khan, Muhammad Umar; Akram, Waheed; Ashraf, Muhammad Furqan; Raza, Muhammad Fahad
Abstract: SNAREs (Soluble N -ethylmaleimide-sensitive factor attachment protein receptors) help intracellular vesicle trafficking and membrane fusion among eukaryotes. They are vital for growth and development of phyto-pathogenic fungi such as Fusarium graminearum which causes Fusarium Head Blight (FHB) of wheat and barley. The SNARE protein Syn8 and its homologues play many roles among different organisms. Here, we have characterized FgSyn8 in F. graminearum as a homologue of Syn8 . We have integrated biochemical, microbiological and molecular genetic approaches to investigate the roles of this protein. Our results reveal that FgSyn8 is indispensable for normal vegetative growth, conidiation, conidial morphology and pathogenicity of F. graminearum . Deoxynivalenol (DON) biochemical assay reveals active participation of this protein in DON production of F. graminearum . This has further been confirmed by the production of bulbous structures among the intercalary hyphae. FgSyn8 mutant strain produced defects in perithecia formation which portrays its role in sexual reproduction. In summary, our results support that the SNARE protein FgSyn8 is required for vegetative growth, sexual reproduction, DON production and pathogenicity of F. graminearum . Highlights: SNAREs help intracellular vesicle trafficking and membrane fusion. The SNARE protein Syn8 play many roles in different organisms. Here, we have characterized FgSyn8 in F. graminearum. The results reveal that FgSyn8 is indispensable for different roles of F. graminearum. Deoxynivalenol (DON) reveals active participation of FgSyn8 in DON production.